Pathological spontaneous activity as a prognostic marker in chronic inflammatory demyelinating polyneuropathy. (9th September 2020) - Grüter, T.; Motte, J.; Fisse, A. L.; Bulut, Y.; Köse, N.; Athanasopoulos, D.; Otto, S.; Yoon, M. ‐S.; Schneider‐Gold, C.; Gold, R.; Pitarokoili, K.
Abstract : Background and purpose: Monitoring of the disease course of patients with chronic inflammatory demyelinating polyneuropathy (CIDP) remains challenging because nerve conduction studies do not adequately correlate with functional disability. The prognostic value of pathological spontaneous activity (PSA) in needle electromyography (EMG) in different CIDP subgroups in a longitudinal context has, to date, not been analysed. We aimed to determine whether PSA was a prognostic marker or a marker of disease activity in a cohort of patients with CIDP. Methods: A total of 127 patients with CIDP spectrum disorder were retrospectively analysed over 57 ± 47 months regarding the occurrence of PSA (fibrillations and positive sharp waves). The presence of PSA at diagnosis, newly occurring PSA, and continuously present PSA were longitudinally correlated with clinical disability using the Inflammatory Neuropathy Cause and Treatment Overall Disability Sum Score (INCAT‐ODSS) and CIDP subtype. Results: Pathological spontaneous activity occurred in 49.6% of all CIDP patients at first diagnosis. More frequent evidence of PSA was significantly associated with a higher INCAT‐ODSS at the last follow‐up. Continuous and new occurrence of PSA were associated with higher degree of disability at the last follow‐up. The majority of patients with sustained evidence of PSA were characterized by an atypical phenotype, higher degree of disability, and the need for escalation of treatment. Conclusions: Pathological spontaneous activity was associated with a higher degree of disability and occurred more frequently in atypical CIDP variants according to the longitudinal data of a large cohort of patients with CIDP. Our results showed that EMG examination was an adequate marker for disease progression and should be evaluated during the disease course.